2019
DOI: 10.1021/acs.est.8b05702
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Antimicrobial Resistance Genes in Manure Blend Pits and Long-Term Storage Across Dairy Farms with Comparisons to Antimicrobial Usage and Residual Concentrations

Abstract: The use of antimicrobials by the livestock industry can lead to the release of unmetabolized antimicrobials and antimicrobial resistance genes (ARG) into the environment. However, the relationship between antimicrobial use, residual antimicrobials, and ARG prevalence within manure is not well understood, specifically across temporal and locationbased scales. The current study determined ARG abundance in untreated manure blend pits and long-term storage systems from 11 conventional and one antimicrobial-free da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 55 publications
4
26
4
Order By: Relevance
“…Among soil samples, the sample from the small organic herd had a diverse pool of ARG including efflux pumps for multidrug resistance, MLS, rifampins, and tetracyclines. As per the history obtained from producers, the soils sampled during spring/summer received manure application about 6-9 months prior to sampling time thus indicating the influence of environmental factors on the distribution of diverse ARG in the soil sample; this is in agreement with the findings of Hurst et al [46] who reported that the abundance of ARG can be influenced by environmental factors such as location, antimicrobial use, farm type, antimicrobial concentrations, and storage of manure samples.…”
Section: Discussionsupporting
confidence: 88%
“…Among soil samples, the sample from the small organic herd had a diverse pool of ARG including efflux pumps for multidrug resistance, MLS, rifampins, and tetracyclines. As per the history obtained from producers, the soils sampled during spring/summer received manure application about 6-9 months prior to sampling time thus indicating the influence of environmental factors on the distribution of diverse ARG in the soil sample; this is in agreement with the findings of Hurst et al [46] who reported that the abundance of ARG can be influenced by environmental factors such as location, antimicrobial use, farm type, antimicrobial concentrations, and storage of manure samples.…”
Section: Discussionsupporting
confidence: 88%
“…We used six manure samples from different farms and treatment stages (untreated, composted, or digested). Five target genes, tetM, tetG, sul1, sul2, and ermB, were chosen because they have frequently been quantified in environmental samples and primer sets are available (25)(26)(27)(28)(29). In the quantitative metagenomic approach, reads were assigned to ARGs in the Comprehensive Antimicrobial Resistance Database (CARD) using graphing resistance out of metagenomes or "GROOT" (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Authors found tet and sul ARGs in chicken layer lagoons were lowest compared with lagoons of swine and dairy facilities. Hurst et al (2019) studied the abundance of 13 ARGs in untreated manure blend pits and long-term storage systems in Northeastern U.S dairy farms, and a majority of farms use a scrape system to collect manure. The authors found ARGs abundance varied among farms, and ARG concentrations generally did not correlate to average antimicrobial usage due to complex environmental factors.…”
Section: Introductionmentioning
confidence: 99%